IMPLIKASI KESEHATAN FISKAL DAERAH TERHADAP EKUITAS NERACA KEUANGAN KABUPATEN KAMPAR 2020 - 2024 - Edi Susanto; Rineliana Rineliana; Yohanisti Yohanisti; Prayetno Prayetno; Omar Farrakhan Tampubolon (Komunitas Manajemen Kompetitif, 2026)
This study examines Regional Fiscal Health (RFH) and its impact on the Balance Sheet Equity of the Kampar Regency Government from 2020 to 2024. Using a quantitative descriptive approach with secondary data from Budget Realization Reports and Regional Balance Sheets, the analysis employs descriptive ratio calculation and Pearson Correlation to test the relationship between Real Budget Deficit (X) and Regional Equity (Y). Findings categorize Kampar's RFH as Moderately Healthy with High Caution, constrained by low fiscal independence and high personnel costs despite successful deficit control. The study confirms a strong negative correlation between Real Budget Deficit and Regional Equity, validating that structural deficits directly erode regional net wealth and weaken long-term solvency. While liquidity remains sound, increasing solvency ratios signal caution. The study recommends urgent structural budget reform focusing on local revenue generation and personnel expenditure efficiency. Consistent deficit control is essential for strengthening Regional Equity and ensuring sustainable fiscal management.